2006
DOI: 10.1001/jama.295.15.1775
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychological and Renal Effects of Dental Amalgam in Children

Abstract: clinicaltrials.gov Identifier: NCT00065988.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
155
1
5

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 233 publications
(168 citation statements)
references
References 29 publications
7
155
1
5
Order By: Relevance
“…22 In a more recent fi ve-year follow-up study examining neurophysiological functions of US children inconsistent differences were found in children with or without amalgam restorations. 23 In an earlier report, the authors Bellinger et al 24 did not find significant differences in adverse neuropsychological or renal effects in children whose caries were restored with dental amalgam compared to those with composite resin. A seven-year follow-up study to assess the safety of Previously diagnosed autoimmune disease was more common in the group with more than 10 amalgams (26.3%), compared with those with 6-10 amalgams (5.6%) or 0-5 amalgams (0%).…”
Section: Discussionmentioning
confidence: 93%
“…22 In a more recent fi ve-year follow-up study examining neurophysiological functions of US children inconsistent differences were found in children with or without amalgam restorations. 23 In an earlier report, the authors Bellinger et al 24 did not find significant differences in adverse neuropsychological or renal effects in children whose caries were restored with dental amalgam compared to those with composite resin. A seven-year follow-up study to assess the safety of Previously diagnosed autoimmune disease was more common in the group with more than 10 amalgams (26.3%), compared with those with 6-10 amalgams (5.6%) or 0-5 amalgams (0%).…”
Section: Discussionmentioning
confidence: 93%
“…Briefly, the NECAT was a two-arm randomized safety trial designed to compare the neuropsychological and renal function of children whose dental caries were restored using amalgam, with those receiving mercury-free composite restorations (Bellinger et al 2006).…”
Section: Methodsmentioning
confidence: 99%
“…After completing baseline data collection visits, these 534 children were randomized to a study treatment arm (amalgam or composite), and received standard dental care every 6 months. Over the course of the study, additional dental restorations were placed as clinically indicated, and according to randomized treatment arm assignment (Bellinger et al 2006). All study procedures were reviewed and approved by Institutional Review Boards at NERI and the respective clinical sites.…”
Section: Recruitmentmentioning
confidence: 99%
See 1 more Smart Citation
“…), dando razão e comentando o artigo do médico Ben Goldacre, colunista do jornal britânico The Guardian, que assina a seção Bad Science (Má Ciência), na qual espinafra as muitas lendas sem lastro científico ou empírico que se propagam como vírus pelos meios de comunicação sobre a fama de vilão do amálgama na odontologia (Goldacre, s.d.). Ao partir para a reabilitação do mercúrio utilizado nas antigas restaurações de amálgama, Goldacre observa, e com muita razão, que nenhum meio de comunicação deu destaque ao primeiro estudo publicado (Bellinger et al, 2006) que usou a metodologia, que se diz consagrada pela medicina, baseada em evidência para procurar dirimir a questão. Acessamos a pesquisa de Bellinger et al (2006), da qual participaram 534 crianças de seis a dez anos, atendidas em clínicas dentárias de Boston.…”
Section: Objeto 'Hollywood Smile'unclassified